KRITERIA PEMIMPIN ISLAM DALAM HADITS - Sunoto (LPPM-IAI BATAM, 2023)
Islam is a religion that has very comprehensive study values, and includes all things, social, political, cultural, economic, and even government and leadership. Today the issue of leaders is often discussed by scholars across disciplines, including Muslim scholars. To this end, this study will attempt to elaborate on the hadiths that are rich in the criteria for leadership in the Qur'an and hadiths. In the Qur'an itself the term leader is often mentioned, and the Qur'an uses several terms about leader. Among them were the Caliph, ulilamri, and priests. Comprehensive discussion of leadership and leadership can be found in various hadiths shahih of the Prophet Muhammad Saw. However, in this study only three hadiths were described, namely hadiths that talked about the criteria of leaders. Hadits first mentioned that the main criteria that leaders must have is faith and trust in Allah SWT. The second Hadits mentioned that the leader should be able to internalize the love relationship with the community he leads. And the third hadith says justice is one of the very crucial criteria that leaders should have.